2000
DOI: 10.1074/jbc.m008040200
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regulation via p38 Mitogen-activated Protein Kinase in Developing Liver

Abstract: During normal development in the rat, hepatocytes undergo marked changes in the rate of proliferation. We have previously observed transient G 1 growth arrest at term, re-activation of proliferation immediately after birth, and a gradual transition to the quiescent adult hepatocyte phenotype after postnatal day 4. We hypothesized that these changes in proliferation are due in part to growth inhibitory effects mediated by the p38 mitogen-activated protein kinase pathway. p38 kinase activity measurements showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
(47 reference statements)
6
45
1
Order By: Relevance
“…Here we describe HGF/SF activation of the ATF-2 transcription factor in 37-32 mouse melanoma cells, and the implication of p38 kinase in the regulation of proliferation, but not motility. In contrast to previous studies in which p38 acted as an inhibitor of cyclin D1 in hepatocytes (Awad et al, 2000), in melanoma cells we found that HGF/SF-mediated induction of proliferation was partially blocked by the speci®c p38-kinase inhibitor SB203580, relative to the complete inhibition observed with the MEK1-speci®c inhibitor PD098059. Although p38 kinase is partially activated through P13K, and P13K has been implicated in HGF/SF-promoted motility (Nakanishi et al, 1999;Lai et al, 2000), we did not observe any e ect on motility by the speci®c p38 kinase inhibitor SB203580.…”
Section: And (E) Indicate Fold Inductioncontrasting
confidence: 99%
“…Here we describe HGF/SF activation of the ATF-2 transcription factor in 37-32 mouse melanoma cells, and the implication of p38 kinase in the regulation of proliferation, but not motility. In contrast to previous studies in which p38 acted as an inhibitor of cyclin D1 in hepatocytes (Awad et al, 2000), in melanoma cells we found that HGF/SF-mediated induction of proliferation was partially blocked by the speci®c p38-kinase inhibitor SB203580, relative to the complete inhibition observed with the MEK1-speci®c inhibitor PD098059. Although p38 kinase is partially activated through P13K, and P13K has been implicated in HGF/SF-promoted motility (Nakanishi et al, 1999;Lai et al, 2000), we did not observe any e ect on motility by the speci®c p38 kinase inhibitor SB203580.…”
Section: And (E) Indicate Fold Inductioncontrasting
confidence: 99%
“…5). This is consistent with previous reports of other cell types showing inhibitory effects of p38 on cyclin D1 expression (29,30). In contrast, expression of p21 was increased in the zones of proliferating and resting chondrocytes in transgenic embryos (Fig.…”
Section: Expression Of a Constitutively Active Mutant Of Mkk6 In Chonsupporting
confidence: 94%
“…Inhibition of p38 kinase activity decreases HNF4α nuclear protein levels and its phosphorylation status in vivo and in vitro, which makes the protein less stable (Xu et al, 2007). Awad et al (2000) and Mendelson et al (1996) reported that p38 MAPK is constitutively active in the liver of adult mice, which is in accordance with our results. In our study, the p38 kinase protein level was significantly decreased in the liver of phenylketonuria-affected mice regardless of age or sex.…”
Section: 05 Vs (A) Pbs Treated Control Cells (P) or Vs (B) Dmso Treasupporting
confidence: 93%